2022
DOI: 10.3389/fped.2022.1018054
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic determinants of Kingella kingae disease

Abstract: Kingella kingae is an emerging pediatric pathogen and is increasingly recognized as a leading etiology of septic arthritis, osteomyelitis, and bacteremia and an occasional cause of endocarditis in young children. The pathogenesis of K. kingae disease begins with colonization of the upper respiratory tract followed by breach of the respiratory epithelial barrier and hematogenous spread to distant sites of infection, primarily the joints, bones, and endocardium. As recognition of K. kingae as a pathogen has incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…K. kingae isolates contain either one or two copies of rtxCrtxAtolC . 7,10,13 To date, little is known about the genomics of K. negevensis due to both a lack of available isolates and a lack of whole genome sequencing. 41 To determine how many RTX loci are present in K. negevensis , we performed Oxford Nanopore Technologies (ONT) MinION sequencing on a collection of 12 isolates (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…K. kingae isolates contain either one or two copies of rtxCrtxAtolC . 7,10,13 To date, little is known about the genomics of K. negevensis due to both a lack of available isolates and a lack of whole genome sequencing. 41 To determine how many RTX loci are present in K. negevensis , we performed Oxford Nanopore Technologies (ONT) MinION sequencing on a collection of 12 isolates (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Recent studies have identified five major virulence determinants that are conserved across this species: type IV pili, a trimeric autotransporter adhesin called Knh, a polysaccharide capsule, an exopolysaccharide, and a broadly active RTX cytotoxin called RtxA. 7 The lipopolysaccharide-associated exopolysaccharide and the RtxA toxin are found only in pathogenic Kingella species. 11,47 In this study, we reconstructed the evolutionary history of rtxA in the pathogenic Kingella species based on a large collection of isolates from both invasive disease and oropharyngeal carriage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Afterward, a breach in the epithelial barrier is required to allow the organism to enter the bloodstream where dissemination to distant sites can take place. Several pathogenic characteristics of K. kingae such as pili, exotoxin, polysaccharide capsule, and galactan exopolysaccharide seem to be essential for the bacteria to survive in the intravascular compartment as well as in various body sites such as endocardium [ 21 ], and these are detailed hereafter.…”
Section: Pathogenicitymentioning
confidence: 99%